The Correlation between the Use of CHATGPT Voice Chat Feature on Pronunciation Among Students at University Level - Muhamad Zaki Ahil Zen; Nasywa Devina Adzra; Asaku Nona Az-Zahra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the correlation between the use of the ChatGPT voice chat feature and pronunciation improvement among university level EFL learners. Using a qualitative literature study design, the research analyzed findings from recent peer-reviewed publications focusing on AI-based pronunciation tools, speech-recognition feedback and learners’ perceptions of ChatGPT-assisted speaking practice. The review shows that ChatGPT voice interaction contributes positively to segmental pronunciation features by providing immediate and accessible corrective feedback, supporting learners’ confidence and motivation in oral practice. The findings also indicate that pronunciation gains particularly in suprasegmental elements such as stress, intonation and rhythm remain modest and less stable compared to improvements in other speaking components. The study concludes that ChatGPT voice chat has a meaningful yet partial impact on pronunciation development, functioning effectively as a supplementary tool when integrated with structured instruction rather than as a standalone method. Keywords: AI-assisted learning, ChatGPT Voice Chat, EFL learners, Pronunciation